Annual report for the year 1989 (CATIE, Turrialba (Costa Rica). Atlantic Zone Programme Ministerio de Agricultura y Ganadería, San José (Costa Rica) Agricultural University Wageningen, Wageningen (Países Bajos), 2014)
38 pág